The Relationship of Elderly Knowledge about Gout and The Incidence of Gout Disease in Posyandu Tempuyung 13 Working Area of Mergangsan Puskesmas Yogyakarta - Anisah, Nurul; Arifah, Siti (Menara Journal of Health Science, 2024)
Uric acid is the breakdown of the waste products from certain foods containing purine nucleotides produced by the body. WHO world health data states that gout sufferers are increasing, especially in developing countries, one of which is Indonesia. Gout data in Yogyakarta in 2022 was 170 people, while the Puskesmas (primary health center) Mergangsan was 11 people. The objective of this research is to determine the relationship between elderly people’s knowledge about gout and the incidence of gout in Posyandu (Elderly Health Unit) Tempuyung 13, Puskesmas Mergangsan Yogyakarta Working Area. The research method used was quantitative analytical observation with a cross sectional research design. The subjects of this research were all elderly people who were present and willing to be respondents at Posyandu Tempuyung 13 Karangkajen, Brontokusuman Subdistrict, Mergangsan District, totaling 65 elderly people. Data analysis used the chi-square test. The results of the bivariate test using the Chi Square test showed a P value of 0.000 (>0.05), so it can be concluded that there was a relationship between elderly people’s knowledge about gout and the incidence of gout at Posyandu Tempuyung 13 Karangkajen, Brontokusuman Village, Mergangsan District, Yogyakarta. There was a relationship between the level of knowledge of the elderly and the incidence of gout, so it is hoped that the elderly who can be helped by their families will pay more attention to the incidence of gout as a preventative and management measure.